2011
DOI: 10.5012/bkcs.2011.32.5.1500
|View full text |Cite
|
Sign up to set email alerts
|

Non-Essential Activation of Co2+and Zn2+on Mushroom Tyrosinase: Kinetic and Structural Stability

Abstract: Tyrosinase is a widespread enzyme with great promising capabilities. The Lineweaver-Burk plots of the catecholase reactions showed that the kinetics of mushroom tyrosinase (MT), activated by Co 2+ and Zn 2+ at different pHs (6, 7, 8 and 9) obeyed the non-essential activation mode. The binding of metal ions to the enzyme increases the maximum velocity of the enzyme due to an increase in the enzyme catalytic constant (k cat ). From the kinetic analysis, dissociation constants of the activator from the enzyme-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…According to the presented results, instead of inhibition by alginate through removal of necessary ions, alginite rathe released metal ions into the assay mixture, resulting in enhanced tyrosinase activity. On the other hand, alginite also has many metal ions [38] that contribute to the functioning of the enzyme, such as Co 2+ , Zn 2+ and Cu 2+ [39,40]. According to the presented results, instead of inhibition by alginate through removal of necessary ions, alginite rather released metal ions into the assay mixture, resulting in enhanced tyrosinase activity.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…According to the presented results, instead of inhibition by alginate through removal of necessary ions, alginite rathe released metal ions into the assay mixture, resulting in enhanced tyrosinase activity. On the other hand, alginite also has many metal ions [38] that contribute to the functioning of the enzyme, such as Co 2+ , Zn 2+ and Cu 2+ [39,40]. According to the presented results, instead of inhibition by alginate through removal of necessary ions, alginite rather released metal ions into the assay mixture, resulting in enhanced tyrosinase activity.…”
Section: Discussionmentioning
confidence: 86%
“…Humic acid can probably bind copper ions similarly (Figure 7). On the other hand, alginite also has many metal ions [38] that contribute to the func tioning of the enzyme, such as Co 2+ , Zn 2+ and Cu 2+ [39,40]. According to the presented results, instead of inhibition by alginate through removal of necessary ions, alginite rathe released metal ions into the assay mixture, resulting in enhanced tyrosinase activity.…”
Section: Discussionmentioning
confidence: 88%
“…That study suggested the conformation change was induced by hydrophobic interactions between the histidine and methionines in the entrance to the active site, making the binding to L-dopa more favorable and inhibiting tyrosine oxidation (33). Current literature also suggests that the activation of mushroom tyrosinase by detergents, metal ions, oligopeptides and catechol-based (substrate) compounds is due to binding of copper ions within the active site that alter the structure and mechanism of oxidation (49)(50)(51)(52). Due to the similarities in enzyme kinetics between the naphthalimides and aarbutin, we conclude that the phenol group of the naphthalimides interacts with the active site and modifies the residues.…”
Section: Modification Of Mushroom Tyrosinase Activitymentioning
confidence: 99%